Lip Laceration and Vermilion Border Repair. (July 2021) - Campo, Theresa M.
Abstract : Lacerations to the face and lips are commonly seen in the emergency setting from dog bites, falls, and blunt trauma (motor vehicle crash, strike with an object, etc.). Lip lacerations, especially involving the vermilion border, can be most challenging and deforming, especially when greater than 25% of the lip is involved. These lacerations require preciseness for a good cosmetic outcome. Lips are a highly visible facial structure and consist of 3 layers: skin, muscle, and oral mucosa. They are used for speech, food consumption, and tactile sensation (Lammers & Scrimshaw, 2019 ; Lent, 2020 ).